Ultrafast carrier phonon dynamics in NaOH-reacted graphite oxide film - Lee, Dongwook (2013)
NaOH-reacted graphite oxide film was prepared by decomposing epoxy groups in graphite oxide into hydroxyl and -ONa groups with NaOH solution. Ultrafast carrier dynamics of the sample were studied by time-resolved transient differential reflection (ΔR/R). The data show two exponential relaxation processes. The slow relaxation process (∼2ps) is ascribed to low energy acoustic phonon mediated scattering. The electron-phonon coupling and first-principles calculation results demonstrate that -OH and -ONa groups in the sample are strongly coupled. Thus, we attribute the fast relaxation process (∼0.17ps) to the coupling of hydroxyl and -ONa groups in the sample.